2016
DOI: 10.3989/scimar.04452.03a
|View full text |Cite
|
Sign up to set email alerts
|

High spatial heterogeneity of two planktonic cnidarian species related to the variability of a shelf-slope front at short time scales

Abstract: Summary:We investigated the variability in the mesoscale distribution of the siphonophore Muggiaea atlantica and the hydromedusa Aglaura hemistoma in relation to the rapid spatial oscillations of the shelf-slope front off the Catalan coast (NW Mediterranean). Three extensive surveys were carried out in spring at ten-day intervals. High variability in the position of the front resulted from the advection of low-salinity waters originating in the Gulf of Lions, mainly from the Rhône River runoff. High spatial va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
0
16
1
Order By: Relevance
“…These studies used methods suited only to sample the larger scyphozoans, such as trawl bycatch and visual survey methods, and were therefore unable to investigate the wider gelatinous assemblage. Where the wider gelatinous assemblage has been sampled, much of the literature reports fronts acting as a barrier between distinct gelatinous communities (Hutchings et al ; Pagès and Gili ; Mianzan and Guerrero ; Graham et al ; Guerrero et al ). In regions where the front separates a warm offshore region from a tidally mixed or an upwelling inshore region, there seems to be greater gelatinous diversity and biomass in the offshore region (Pagès et al ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies used methods suited only to sample the larger scyphozoans, such as trawl bycatch and visual survey methods, and were therefore unable to investigate the wider gelatinous assemblage. Where the wider gelatinous assemblage has been sampled, much of the literature reports fronts acting as a barrier between distinct gelatinous communities (Hutchings et al ; Pagès and Gili ; Mianzan and Guerrero ; Graham et al ; Guerrero et al ). In regions where the front separates a warm offshore region from a tidally mixed or an upwelling inshore region, there seems to be greater gelatinous diversity and biomass in the offshore region (Pagès et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results here, where there was a slight increase in gelatinous biomass moving away from the front, and an obvious increase in diversity in the warm water gelatinous community. Gelatinous biomass does not always increase in the offshore regions, as demonstrated by the increased hydrozoan abundance on the shoreward side of the Catalan front (Guerrero et al ). However, an increase in diversity with the oceanic influence is well‐reported (Mackie et al ; Pagès and Gili ; Mianzan and Guerrero ; Graham et al ), and Pagès et al () suggested that the warm stable conditions in stratified water provided a favorable environment for gelatinous taxa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For both CCA analyses, the collinearity between pairs of environmental variables was evaluated by pairwise scatterplots and Pearson’s correlation coefficients with a cut-off value of |0.5| [ 33 ]. The variables chlorophyll a and salinity were collinear, and salinity was retained for the analyses because it was previously observed to be one of the most determinant parameters in the distribution of planktonic cnidarians in the area [ 37 , 38 ]. The species matrix used in all the statistical analyses was composed by those species with more than five presences (individuals) and/or present in more than 2 stations during the three surveys.…”
Section: Methodsmentioning
confidence: 99%